Ultrasonic blood fractionation: whole blood behaviour in an ultrasonic field - Nathan, Malavika (My University, 2020)
Fractionation of blood into its individual components is useful for diagnostic purposes. Ultrasound is a safe, non-invasive and affordable technology that can be implemented as an option for blood component fractionation, simply understood as component separation, based on the theory that mechanical sound fields can force cells to behave differently depending on its particular mechanical makeup. In this study, the proposed method of ultrasonic blood fractionation is investigated as an alternative to existing methods. A specialised experimental set-up is designed and built to observe blood cell translation subjected to ultrasound. Red blood cell movement is more pronounced, moving in the opposite direction to white blood cells. White blood cells are only restricted in movement when trapped in a concentrated sample, not moving as much as when in a diluted sample. Erupted white blood cells move in a unique manner, different to intact white blood cells and red blood cells. Prolonged exposure to ultrasound results in white blood cell membrane expansion and ultimate eruption. The samples used were from blood banks thus the effects need to be repeated on fresh samples of blood for verification. It is concluded that ex-posing whole blood to ultrasound is capable of separating different components, however, more intense research in this field can verify the extent of its application as a separate technology that can compete in the industry. This research forms a basis into the application of an alternative means to separate whole blood into separate components without damaging cells by using fundamental resonance properties of the cells as a means to separate the constituents. In addition, this research has establish groundwork necessary to be extended in a field relating to parasite-infested cell purification and further studies. The outcome of the experimental results can be used to explore if ultrasonic technology is viable in an extended application of separating healthy and parasitic blood cells, for example healthy and malaria-infested red blood cells, ex-vivo similar to a dialysis machine
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Science in Engineering, 2020